Aprendizagem ativa de matemática na educação de jovens e adultos - Lorenzoni, Sandra Mara de Almeida (2022)
The present research proposes a study about the curricular methodologies in the teaching of mathematics for the modality of Education of Youths and Adults - EJA final years, guided by the following questions: "How can we prepare lesson plans that fit into the teaching modality? of EJA? “How to organize workshops of practical activities with students so that they can develop content knowledge? “What are the changes felt and effectively practiced by the students after the construction of knowledge related to the new methodologies? In this sense, the objective was to list a theoretical reference on the methodologies to be worked on in the discipline of mathematics, which could meet the needs of the public attending this type of education. Therefore, it was necessary to take into account the mathematics curriculum and its concepts present in official documents such as the National Curricular Common Base - BNCC. Thus, this research also aims to guide the teacher's work with the specific needs of these students, proposing alternatives that are significant to the educational practices developed in EJA. Therefore, the academic relevance of this research lies in the contribution to enhance the teacher's knowledge and consequently contribute to the Meaningful Learning of students, through active methodologies. Qualitative research was used in this study and, initially, a literature review and document analysis were carried out, using the case study approach. The participating subjects were 20 elementary school students, final years of EJA Phase 7 and 8 and it was carried out in a school of the state teaching network of the night shift in the city of Manaus-AM, located in the Center, they participated in practical and theoretical classes about the Power content. Among the teaching methodologies, a data collection was carried out from the students' Concept Maps after the application of the activities. As for the theoretical approach, this was supported by authors such as: Bizzo (2012); Brazil (1997); Falssarela (2004); Freire (1996); Seixas (2017), among others that enabled the reflections carried out in this research. Therefore, it was found that the results presented showed that the Conceptual Maps applied as a teaching methodology favored student learning, motivating and helping them to solve mathematical problems. Keywords: EJA Final Years. Active Methodologies. Concept Maps. Mathematics Curriculum.